Zine Pedagogies: Students as Critical Makers - Scheper, Jeanne (Radical Teacher, 2023)
In this essay, I talk about what zines are, why zine-making fosters an “ethos” which is a particularly good fit for the feminist critical cultural studies classroom, and how I utilize zines in gender and sexuality studies in order to teach about the value and existence of community archiving practices and queer history-making. I share both the theoretical underpinnings of this pedagogical work, as well as the practical “how-tos” of teaching with zines, including the application of five key principles to scaffolding learning and developing the analytic tools of cultural critique through the zine project assignment.